Electro-goniometric system: an instrumentation to capture knee movements for forward walking - Akhtaruzzaman, Md.; Shafie, Amir Akramin; Khan, Md. Raisuddin (IEEE, 2015)
Continuous monitoring, accuracy of evaluation, and proper analysis of human gait characteristics have presented the importance not only in clinical studies, but also in the field of sports, rehabilitation, training, and robotics research. Human knee joint plays an important role in balancing and stabilizing human body while walking. So it is obvious to observe knee joint movement characteristics as a part of gait analysis. In this paper, instrumentation for capturing knee joint movement pattern is presented. The instrumentation is designed based on Electro-goniometric mechanism with flexible joints on arms that attached with upper and lower extremity of lower limbs. The electrical signals obtained from the instrumentation are calibrated carefully to present the movement angles in degree. The instrumentation system is viable to represent knee movement pattern of human walking which is compared with the result of image based analysis.